Determinants of mobile money subscriptions induced by conventional banks in Sub-Saharan Africa. - Banda, Msinje (Graduate School of Business (GSB), 2024)
Mobile Money is labelled essential for financial inclusion and financial access in countries subject to low bank penetration and dispersion. Mobile Money has proven to reach utmost rural areas in Africa, by providing financial access which several commercial banks have struggled to achieve since inception. The cost of Mobile Money penetration in comparison to incumbent banking penetration are apart by massive margins, mainly based on tedious registration requirements and high infrastructure costs faced by commercial banks. The empirical research report methodology issues such as endogeneity bias, heteroscedasticity, serial correlation, significant coefficient selection and valid instrument selection measured in the short and long run. Mobile money is termed disruptive when undertaken by mobile network operators that eventually become quasi- or virtual banks, and exceedingly profitable when undertaken by commercial banks. What is unclear is how long these disruptions last before conventional banks latch on and hence the questions being put forward. This paper examines the level of disruption fintech vices such as mobile money, remain influenced by reduced traditional commercial bank operations. The study employs quantitative analysis on secondary panel pooled data over the period 2010-2019. It analysed the short-run and long run dynamics of interaction between several facets that constitute traditional bank operations and mobile money subscriptions. This study critically analyses fourtraditional bank related conduits namely, Automated Teller Machines (ATM) to commercial branch dilution, commercial bank transaction value and commercial bank transaction volume. While mobile money components such as active mobile money subscriptions and mobile money agents are examined, the empirical model was estimated using the two-stage least-squares and the twostep system generalised method of moments technique. Hence, the key question this study poses is how mobile money subscriptions have significantly been affected by traditional banking payment mechanisms, in the short and long run within SSA. The empirical findings exhibited a significant relationship with the interaction between mobile money on traditional banking conduits such as automated teller machines within SSA and REC ECOWAS. This interaction revealed the positive long run effect increased commercial bank has on mobile money subscriptions, insinuating industry convergence. However, this study could not establish whether strong regulated banking institutions implied contrary results in parts of SADC. Keywords: Secondary panel pooled data; ATM to branch dilution; registered mobile money subscriptions; Two stage least-squares; Two step system generalised method of moments; SSA.